Interleukin‐6 increases adrenal androgen release by regulating the expression of steroidogenic proteins in NCI‐H295R cells. Issue 12 (28th April 2020) - Wei, Xian; Zhang, Junfeng; Peng, Wei; Xu, Hao; Wei, Zhewen; Pang, Linhao; Liu, Jihong; Wang, Tao
Abstract: The purpose of this study was to investigate the potential mechanism of interleukin‐6 (IL‐6) on the stimulation of excessive androgen secretion in human NCI‐H295R adrenocortical cells. We performed transcriptome sequencing of cancer and paracancerous tissues obtained from functional adrenal cortical adenomas. The secretion of dehydroepiandrosterone sulfate (DHEAS) in NCI‐H295R cells was detected by a chemiluminescence assay. The expression of messenger RNA (mRNA) was detected by real‐time polymerase chain reaction and that of protein was detected by western blotting. The expression of secretogranin II (SCG2) and IL‐6 were significantly increased in cancer tissues. Upregulation of mRNA and protein levels of AKR1C3, CYP11A, CYP17A1, 3βHSD, and SULT2A1 was observed after stimulation with IL‐6. IL‐6 could also increase the expression of StAR mRNA and proteins. Our results suggest that IL‐6 can promote androgen secretion by regulating the expression of genes related to androgen pathways. Abstract : The mechanism by which interleukin‐6 (IL‐6) stimulates adrenal androgen overproduction is unknown. We found that the IL‐6 can promote androgen secretion by regulating the expression of genes related to androgen pathways.